The Role of TPQ in Improving Quality Qur'an Reading Ability in Children at TPQ Al-Hirro Kampung Anyar, Tegal Village - Nurada, Alda Munjilatu; Hikmah, Barikatul; Alvian, Raihana Jilan (LPPM UIKA Bogor, 2024)
The purpose of this research was to obtain information about the role of TPQ in improving the quality of reading the Qur'an in children and knowing what obstacles are experienced in learning the Qur'an at TPQ al-hirro. The research method in the preparation of this scientific paper uses qualitative research. Sourced from the results of research up to It can be concluded that TPQ Al-Hirro has made efforts to optimize the improvement of Al-Quran reading skills in early childhood at TPQ Alhirro with the movement of TPQ management in organizing, monitoring, and centralizing effective and efficient Al-Quran learning activities, not only with a real vision and goals and various methods to improve Al-Quran reading skills in early childhood and adolescents. From this research, it can also be known what obstacles and obstacles exist in TPQ al-hirro, both internal and external, in an effort to improve the quality of reading the Quran.